The frailty syndrome in older adults with type 2 diabetes mellitus and associated factors - Bartolomeu Fagundes de Lima Filho; Antônia Gilvanete Duarte Gama; Vanessa da Nóbrega Dias; Eliza Mikaele Tavares da Silva; Fabricia Azevedo da Costa Cavalcanti; Juliana Maria Gazzola (Revista Brasileira de Geriatria e Gerontologia, 2020)
Abstract Objective: To compare clinical-functional factors among groups in relation to the frailty syndrome (pre-frail and frail) phenotype profile in older adults with type 2 diabetes mellitus (DM 2). Methods: A descriptive, analytical, cross-sectional study with a quantitative approach was performed. A total of 113 diabetic older adults of both sexes were evaluated in terms of their personal, socio-demographic, clinical-functional, mental, cognitive and fragility phenotype data. The Chi-square test and a logistic regression model were used. Results: The mean age was 68.66±6.62 years, and the sample was mostly female (61.9%), illiterate or with an incomplete primary education (60.2%), pre-frail (52.2%), sedentary (79.6%), and had been diagnosed with DM2 for more than 5 years (58.3%). There was a significant association between “pre-frail and frail” individuals and schooling (p=0.004), social participation (p=0.004), a subjective perception of vision (p=0.004), glycated hemoglobin (p=0.036), limb pain (p=0.012), depressive symptoms (p=0.002) and mobility (p=0.004). The logistic regression model showed an accuracy of 93.6% and the significant variables were education (p=0.039), pain in the lower limbs (p=0.025) and risk of falls (p=0.033). Conclusion: among all the factors related to the “pre-frail” and “frail” phenotype, schooling, pain in the lower limbs and mobility were most related to the worsening of the syndrome and its progress.